E-module development of lathe machinery engineering mechanical engineering expertise program - Suparmin Suparmin; Setuju Setuju; Hero Purnomo; Hasnul Azwan bin Azizan; Muh Rafiq Alghozali (Jurnal Taman Vokasi, 2022)
The research objectives were to: (1) Describe the process of developing e-module lathe machining techniques for class XI SMK. (2) Knowing the feasibility of e-module lathe machining techniques class XI SMK. This research includes a mixed type of qualitative and quantitative research called research and development (Research and Development). The development of this teaching material uses the 4D research and development model which consists of the define , design , development and dissemination . The subjects in this study consisted of material experts and media experts, namely PVTM UST Yogyakarta study program lecturers, as well as class XI students majoring in Mechanical Engineering SMK as users of the developed learning media. Data collection techniques using Google Forms and observation. Data analysis techniques use qualitative and quantitative descriptive approaches. (3) The results of this study are e-modules/electronic modules for lathe machining techniques. The e-module was declared good for use based on due diligence according to material experts with a total percentage of 79.7%, media experts with a total percentage of 77.9%, small group test results with a total percentage of 79.6% and large group trials with a total percentage of 83.6%. (4) Based on these data, the class XI lathe machining technique e-module is very suitable for use in learning.